Mapping the individual professional development journeys of teachers in an Indian school setup - Eidnani, Shweta (2019)
Professional development of teachers has been a topic of exploration, scrutiny, and debate for the past decades. Numerous studies and researchers around the world have made valuable contributions into defining and explaining the concept of professional development, as well as many, have contributed to outlining the process of professional development. This research has impacted the planning and implementation of professional development programs, rightly so. In India, teacher professional development is a comparatively neglected area of education, the major focus is on delivering content and skills to the teachers in order to achieve improved student outcomes. This action research addresses the journey of professional development within a school community which is a part of the Akanksha Foundation. The study spans over a period of two months and has three teacher participants. In doing so this study focuses on training the teachers to use the 4C framework in order to enhance their professional competencies such as planning and implementation of lessons. This study goes on to map the individual journeys of these participants while they adapt and implement practices based on the 4C framework. Alongside, it also explores the impact of implementing new practices on a teacher’s mental and emotional well-being. Thus, highlighting the various personal and professional factors that impact this process in a negative or a positive way.